KEANEKARAGAMAN TUMBUHAN ANGIOSPERMAE DI HUTAN KOTA MALABAR, KOTA MALANG, JAWA TIMUR - Putri, Erisa Alifia; Rahmania, Almasinta Dyah; 'Ainunnizar, Desy Fitriaska; Listiandi, Jovano Andrew; Reswara, Talitha Raissa; Sutiyani, Tarisah; Fardhani, Indra (Universitas Pakuan, 2023)
The geographical area that belongs to Indonesia makes for a high diversity of plants. With so much diversity, it makes an area inhabited by certain species. One of these species is the Angiosperms, especially the dicot plants (in two pieces) which dominate the variety of plants in the Malabar City Forest, Malang City. Therefore, based on the previous description, this research will focus on the diversity of Angiosperm plants found in the Malabar City Forest, Malang City. The purpose of this study was to determine the diversity of dicot and monocot plants (Angiosperms) found in Malabar Malang City Forest. This research was conducted in the Malabar City Forest area of Malang City, East Java. The sampling technique used was to make three plots, 5 m x 5 m. Based on the results of research conducted on three plots in the Malabar City Forest of Malang City, 12 species of dicot plants were obtained which were divided into 9 families and 4 types of monocot plants which were divided into 3 families.